Population, Reproduction And Fertility In Melanesia - Ulijaszek, Stanley J. (Fertility, reproduction, and sexuality., 2013)
Human biological fertility was considered a important issue to anthropologists and colonial administrators in the first part of the 20th century, as a dramatic decline in population was observed in many regions. However, the total demise of Melanesian populations predicted by some never happened; on the contrary, a rapid population increase took place for the second part of the 20th century. This volume explores relationships between human fertility and reproduction, subsistence systems, the symbolic use of ideas of fertility and reproduction in linking landscape to individuals and population.